Business Potential of Arctic Berry Wax for Cosmetics in the UK : Wax Project - Cao Thi Dieu, Phuong (Oulun ammattikorkeakoulu, 2018)
The Bachelor’s thesis examines strengths and weaknesses of Arctic berry wax and analyzes the natural cosmetics industry for the multi-disciplinary Wax Project with the participation of many Nordic universities. The project researches the environmentally sustainable methods to extract Nordic wild berry wax from industrial side streams and waste. Based on researching the methods, the applications of the wax in different fields are also studied with the goal of creating a new high-quality and valuable Arctic berry wax-based product. The project consists of different work packages and identifying its business opportunities is a section of the whole project and thereby, the project can raise its funding and collaborate with business partners. The research aims to explore the business potential of Arctic berry wax for cosmetics in the United Kingdom. Based on the analysis of the ingredient and natural cosmetics market, the frameworks of SWOT and Value Proposition will be drawn so that readers will have an extensive insight into exceptional properties of the wax. Moreover, these frameworks are beneficial for natural cosmetics companies which plan to access the British market. With the help of a variety of analysis models concerning marketing research, the values of berry wax and the business markets of natural cosmetics industry are clarified. In addition to theoretical background, to obtain a practical view towards the subject, a qualitative interview with an experienced expert in this field is conducted. On the basis of the wax and market research, it is claimed that the UK is an exceedingly potential market for natural cosmetics, including wild berry-based products. The market promisingly offers a range of business opportunities for the supplementary ingredient with the continuous growth of value sales and customer shift towards natural cosmetics. Along with it, due to the aggressive market, cosmetics companies will face a few challenges. However, as Arctic berries possess unique characteristics, natural cosmetics ...